Contribution of lean and Six Sigma to effective cost of quality management. (1st January 2014) - Jourabchi, S.M. Mehdi; Arabian, Tina; Leman, Z.; Ismail, Md. Yusof B.
In today's competitive market, most of the organisations promote quality as a critical success factor to achieve sustainable competitive advantages when the high quality of delivered product and service is considered extensively by the customers as a vital factor besides a reasonable price. Hence, most organisations would invest a lot of money to achieve the desired quality, at the same time, set a competitive price. Although, various quality improvement models, methods and tools can be applied to determine the most effective areas and the level of investment needed to measure, control and manage the cost of quality (COQ). This paper tries to present and summarise COQ models to identify COQ elements by emphasising the optimal quality cost model to see how lean and six sigma approaches can contribute to achieve further improvement in terms of reducing waste, time, defects and variation while targeting and obtaining the minimum total quality costs.